Discrete (Two-State) Modular Hyper-Redundant Planar Manipulator - Zawidzka, Ela; Zawidzki, Machi (Computer Assisted Methods in Engineering and Science, 2022)
This paper presents a concept of an extremely simple planar manipulator composed of 24 congruent modules. Each module has only two possible discrete positions in relation to the previous module: left (-π/6) or right (π/6).  However, despite its conceptual simplicity, this manipulator can perform relatively demanding tasks, for  example as an inspection device. The manipulator is placed in an experimental environment, and the goal is to place its tip in close proximity to five given points without collisions. Despite the constraints of its motion, the manipulator effectively “crawls” inside the working space and visits assigned points. The control of the manipulator is executed by manual placing to desired configurations and interpolating the intermediate transitions. The preliminary results are promising and show that for certain practical types of tasks, the functionality and precision of this extremely simple manipulator could be sufficient, e.g., visual inspection, provision of survival supplies, placing of explosives, etc.